Pusat Pengetahuan , Komunikasi Dan Teknologi (PPKT) Kampus Kesihatan, Kubang Kerian Kelantan / Muhammad Firdaus Wahid - Wahid, Muhammad Firdaus (Perpustakaan Tengku Anis, 2018)
In this report, its provide a comprehensive description about the practical training which is are being carried out at Pusat Pengetahuan, Komunikasi Dan Teknologi (PPKn Kampus Kesihatan, USM Kubang Kerian for 5 months period. There are 4 chapter's content which include introduction to an organization which are USM Kubang Kerian and Pusat Pengetahuan, Komunikasi Dan Teknologi (PPKT). Various department which carry a different role and different job scopes, than the activities that are carried out during the practical training and lastly the lesson gained during the time period of training.